Calidad del servicio del almacén “La Casa De Los Tapices” De La Ciudad De Babahoyo. - Macias Manzano, Zullimen Elena (2022)
User quality is a relevant component that the commercial management of any business organization must take care of, because it directly influences the perception of the consumer market and the level of sales. Therefore, it is a key factor for organizational success in companies, regardless of the economic activity in which they are engaged. The objective of this case study is to determine the user's perception of the customer service process provided by the human talent of the store "La Casa de los Tapices". The methodology used is constituted by a mixed approach, quali-quantitative, in addition, descriptive and field research types were used; while the method employed was the inductive one, where the main research findings were segregated for the elaboration of general conclusions. The techniques used are; a survey directed to the customers of the store to determine the perception they have about the attention received and an interview to the manager-owner of the establishment to identify the organizational weaknesses that condition the quality of the user. The results of the investigation reveal that the human talent does not develop adequate human relations that strengthen the commercial processes with the clients, in the same way it was identified that the organizational management has not implemented internal analysis and business strategies to strengthen ties with the clients.